Metadiscourse within a discipline: A study of introduction and literature review chapters of sociology masters’ theses - Akoto, Osei Yaw (Universitas Pendidikan Indonesia, 2020)
It has been established that there are inter-chapter variations regarding metadiscourse use in masters’ thesis. This paper, therefore, investigates the differences and similarities in metadiscourse use between the Introduction and Literature Review (LR) chapters in Sociology masters’ thesis from an English-medium university. The Introduction and LR Chapters of ten theses constituted the corpus for this study. The metadiscursive devices were manually coded, drawing on the modified version of the Hyland’s (2005a) interpersonal model of metadiscourse. It was realized that there are both differences and similarities between the two chapters in terms of metadiscourse use. In the ranking, the interactive and interactional devices, transitions, and hedges respectively recorded the highest frequencies in the two chapters. Besides, there were significant variations across the two chapters in terms of both interactive and interactional subcategories. The findings have implications for the teaching of English for Research Purposes, and the theory of metadiscourse.